Pengaruh Kualitas Pelayanan Dan Citra Merek Terhadap Kepuasan Konsumen Pada Pt. Mitra Dewata Sukses (J&T Express) Di Denpasar Utara - Putri, Putu Bela Aliani; Suartina, I Wayan (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Consumer goals play an important role for the life and development of a company, as well as a product because consumers ultimately decide to choose at least one choice between the two available options. consumer goals can be determined by the quality of service provided and the brand image owned by a company. The purpose of this study was to determine the effect of service quality and brand image on consumer satisfaction. This research was conducted at PT Mitra Dewata Sukses (J&T Express) in North Denpasar with a total population of 351,368 consumers. Determining the number of samples was done by accidental sampling method and using the Slovin formula so that the number of samples was determined to be 100 people. Primary data collection is done by using a questionnaire. Hypothesis testing is done by using multiple linear regression analysis. Based on the results of the analysis, it can be found that (1) service quality has a positive and significant effect on consumer satisfaction, (2) brand image has a positive and significant effect on customer satisfaction, (3) service quality and brand image have a positive and significant effect on customer satisfaction